Bioavailability of metals in soils irrigated by synthetic wastewater - Korfali, S.I. (2017)
In Lebanon, Bekaa valley is an agricultural zone; during the dry season, water is withdrawn from Litani River for irrigation which is mostly domestic and industrial waste water. Metal mobility, bioavailability, or potential risks can be anticipated by metal speciation in soil and water. The objective of this study was to investigate the speciation of metals in soil and water of upper Litani basin. Soils samples were subjected to a modified BCR sequential extraction technique that operationally extracts metals as acid soluble, reducible, oxidizing, and residual fraction. Metal content in each fraction and total metal in water were determined by AAS and ICP-MS techniques. Sediment pH, Eh and TOC and macro water parameter were determined. Speciation of metals in water was predicted PHREEQC geochemical computer model. Results indicated in non-residual fraction respectively highest average % of total metal are in reducible and acid soluble (Mn: 27 %, 18; Zn: 18 %; Cr: 27%, 34%; As: 28% , 20%); in oxidizing and acid soluble (Cu: 25%, 10%; Ni: 24%, 33%; Cd: 16%, 23%, Hg: 23;%, 12%). Metal speciation variations among sites were related to the levels of TOC and Eh and water BOD. The ICF values indicate a considerable contamination for As, Cd, Cr, Ni; and GCF indicated 50 % of sites of considerable contamination. Speciation in water predicted existence of the toxic free aqua ion (Mn: 6-97%; Zn: 35-89%; Ni: 60-90%; Cd: 35-82%). These and soil GCF values reflect the high degree of metal bioavailability, toxicity, and potential risk.